Pengaruh Corporate Social Responsibility, Cash Holding, Profitabilitas, Kebijakan Dividen, dan Kepemilikan Institusional Terhadap Nilai Perusahaan - Diparma, Shafira Hakim Dara; Kusumawati, Eny (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
Company value is a certain condition achieved by a company as an indication of public trust in the company after carrying out an activity for several years, namely since the company was founded until now. This study aims to analyze the effect of corporate social responsibility, cash holding, profitability, dividend policy, and institutional ownership on firm value in an empirical study of non-financial companies on the Indonesia Stock Exchange in 2019-2021. The sampling technique used purposive sampling which obtained 226 data. The results of the study provide empirical evidence that profitability and dividend policy have affect firm value. Meanwhile, corporate responsibility, cash holding, and institutional ownership have no effect on firm value.